Pelaksanaan Nagari Binaan Pilot Proyek di Nagari-nagari Sumatera Barat - Rafni, Al (Jurnal Demokrasi, 2011)
The establishment of â€œNagari Binaanâ€ aims to realize the Nagari that could empower and capable of performing a real autonomy and responsible with all the strength of its resources. All of the efforts are aiming to provide optimum services for the community of the Nagari (village). This article focuses on the study of development programs and constraints faced in the implementation of the project. The findings of this study showed that of the 11 districts that made â€‹â€‹coaching pilot project in general showed varying successes. The obstacles encountered this project are: coordination and synchronization program, the effectiveness of program delivery mechanisms, and community support. Kata Kunci: Nagari Binaan, Evaluasi Program, Penyelenggaraan pemerintaan nagari